Frequency and predictors of postoperative atrial fibrillation development after aortic valve replacement in patients with aortic stenosis - F. Hassanzadeh Ghasabeh; B.M. Todurov; I.Yu. Mokryk (Медицина неотложных состояний)
Background. Aortic stenosis is the most frequent form of heart valve pathology, the prevalence of which increases with age. Calcification of the bicuspid aortic valve and degenerative changes of the tricuspid valve are the most common causes of surgical intervention. Currently, there is no effective pharmacological treatment for this pathology, so surgical aortic valve replacement is the gold standard. Despite the introduction of new methods of surgical treatment, improvements in myocardial protection techniques and anesthetic support, more than half of patients undergoing aortic valve replacement develop postoperative atrial fibrillation (POAF) associated with increased morbidity, mortality, extended hospitalization, and higher healthcare costs. Today, this issue is not insufficiently explored, in particular, the frequency of POAF varies with different types of surgical intervention, and the predictors of its occurrence differ in patients with aortic stenosis and aortic regurgitation, because stenosis and dilated heart cavities have radically different pathophysiology and intracardiac hemodynamics. Objective: to determine the frequency of POAF and risk factors for its development in patients with aortic stenosis who underwent aortic valve replacement. Materials and methods. The study included 196 patients with aortic stenosis, 112 men and 84 women aged 36 to 83 (average of 63.77 ± 8.59) years, who underwent aortic valve replacement. They were divided into 2 groups: group I — 82 people who developed POAF, group II — 114 patients without heart rhythm problems. A comparison of demographic, preoperative general clinical, instrumental and electrophysiological indicators, as well as intraoperative and early postoperative parameters was carried out. Results. POAF developed in 82 (41.8 %) of 196 patients with aortic stenosis who underwent aortic valve replacement. Group I significantly more often had coronary heart disease, stage III chronic kidney disease, history of COVID-19, moderate mitral valve regurgitation and bicuspid aortic valve. With the help of receiver operating characteristic (ROC) analysis, the cut-off points of the following preoperative indicators for predicting POAF development were calculated: aortic valve area (area under the ROC curve (AUROC) 0.388; 95% confidence interval (CI) 0.290–0.485) at cut-off < 0.75 cm2, left atrial volume (AUROC 0.653; 95% CI 0.575–0.73) and left atrial volume index (AUROC 0.651; 95% CI 0.572–0.731) at cut-off > 85.5 ml and > 45.07 ml/m2, accordingly, platelet (AUROC 0.389; 95% CI 0.306–0.471), blood glucose (AUROC 0.657; 95% CI 0.541–0.772), thyroid-stimulating hormone (AUROC 0.725; 95% CI 0.632–0.818), creatinine level (AUROC 0.738; 0.663–0.813; р < 0.001) and glomerular filtration rate (AUROC 0.35; 95% CI 0.272–0.428) at cut-off < 210.5 × 10⁹/l, > 6.05 mmol/l, > 5.15 mU/l, > 85.5 mmol/l and < 51.9 ml/min, accordingly. The use of median sternotomy as a method of surgical access was found to be reliable and was associated with a higher risk of POAF (odds ratio 1.91; 95% CI 1.05–3.48). Conclusions. The frequency of postoperative atrial fibrillation in patients with aortic stenosis who underwent aortic valve replacement was 41.8 %. Significant risk factors for POAF were coronary heart disease, stage III chronic kidney disease, history of COVID-19, bicuspid aortic valve, moderate mitral valve regurgitation, aortic valve area < 0.75 cm2, increased left atrial volume > 85.5 ml and left atrial volume index > 45.07 ml/m2, decreased level of platelets < 210.5 × 109/l, increased blood glucose > 6.05 mmol/l, thyroid-stimulating hormone > 5.15 mU/l, creatinine > 85.5 mmol/l and decreased glomerular filtration rate < 51.9 ml/min, surgical access through median sternotomy. The identified predictors of POAF allow for the development of the prognostic model of risks, as well as an effective strategy for heart rhythm disorder prevention in this cohort.